TRANSFORMATION OF THE IMPACT OF EDUCATION ON THE FORMATION OF A CULTURE OF PROFESSIONALS AND SUSTAINABLE DEVELOPMENT - Kinash, Iryna Petrivna; Kutsenko, Vira (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article indicates that recently, on the one hand, the role played by education in ensuring sustainable development has been increasing, and on the other hand, there has been a decline in its prestige, despite the fact that in the country, as in the world as a whole, the knowledge economy is being formed. This is associated with transformational changes not only in the economy, society, but also in education itself. The study of this issue presented in the article is aimed at ensuring the acceleration of transformation processes in education. At the same time, special attention is paid to the problems of strengthening the interaction between educational institutions and business, education system and employers, improving the quality of education, improving its content. The latter should be based on: humanization, humanitarization, fundamentalization, technologization, informatization, continuity of education and its effectiveness. It is emphasized that the priority role in achieving qualitative changes as a result of transformational processes in the educational sphere belongs to the active implementation of scientific and technological progress in the educational process, which, in turn, requires certain changes in the work of an educational institution, in particular in terms of the use of modern pedagogical technologies, training, as well as theoretical knowledge, appropriate methodology. It is noted that the transformation of education should be aimed at ensuring the advanced development of its potential on an innovative basis. The ways of achieving this are given, including: the search for new forms and organizational structures of education; identifying the causes of negative phenomena in the development of education (such as chronic underfunding), overcoming such negative phenomena as the provision of low-quality educational services; accelerating the formation of educational, scientific and innovative complexes in Ukraine, the activities of which have a significant impact on the formation of a new rapidly changing market of educational services, on the active introduction of innovative technologies in the production of goods and services. The substantiation is given that in the future the transformation of the educational factor contributing to sustainable development should be aimed at achieving the goal of training specialists who are ready to successfully solve various educational problems, skillfully use their knowledge and constantly master new technologies, and achieve European quality standards knowledge and the like.